2001
DOI: 10.1063/1.1418452
|View full text |Cite
|
Sign up to set email alerts
|

Current collapse and the role of carbon in AlGaN/GaN high electron mobility transistors grown by metalorganic vapor-phase epitaxy

Abstract: The two deep traps responsible for current collapse in AlGaN/GaN high electron mobility transistors grown by metalorganic vapor-phase epitaxy have been studied by photoionization spectroscopy. Varying the growth pressure of the high resistivity GaN buffer layer results in a change in the deep trap incorporation that is reflected in the observed current collapse. Variations in the measured trap concentrations with growth pressure and carbon incorporation indicate that the deepest trap is a carbon-related defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
192
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(211 citation statements)
references
References 14 publications
13
192
1
1
Order By: Relevance
“…The spectra of the MBE-grown devices are distinctly different from any of the spectra previously obtained from MOCVD structures. Discussion: The absence of a trap2 feature in the absorption spectrum of MBE-grown devices is consistent with the recent association [8] of this defect with the presence of carbon in MOCVD-grown structures. While carbon is one of the primary unintentional impurities in MOCVDgrown materials as a result of the organic precursors employed in the growth, it is not expected in MBE materials in substantial concentrations.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The spectra of the MBE-grown devices are distinctly different from any of the spectra previously obtained from MOCVD structures. Discussion: The absence of a trap2 feature in the absorption spectrum of MBE-grown devices is consistent with the recent association [8] of this defect with the presence of carbon in MOCVD-grown structures. While carbon is one of the primary unintentional impurities in MOCVDgrown materials as a result of the organic precursors employed in the growth, it is not expected in MBE materials in substantial concentrations.…”
supporting
confidence: 66%
“…Both traps have also been associated with persistent photoconductivity in GaN. Trap1 appears to be a strongly lattice-coupled deep donor [3,7] and trap2 has been identified [8] as a carbon-related defect.…”
mentioning
confidence: 98%
“…Using photocurrent spectra, Dang et al 36 found continuous trap levels between 2.2 and 3.4 eV in both AlGaN barrier and GaN buffer. Using photoionization spectroscopy, Klein and co-workers 27,40 found the same trap levels in the GaN buffer of AlGaN/GaN HFETs as they had previously found in GaN MESFETs. 38 Using deeplevel optical spectroscopy, Nakano et al 41 identified trap levels of $1.70 and $2.08 eV at the AlGaN/GaN interface.…”
Section: Investigation Of Trap Levels Using Monochromatic Irradiationmentioning
confidence: 68%
“…Although the location of these traps cannot yet be specified, similar density values have also been reported for the traps on AlGaN surface [24][25][26] and in GaN buffer. 27,28 The possible location of the observed traps will be discussed in the following subsections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation